Stereoselective Intramolecular Carbene C–H Insertion Catalyzed by Rhodium(III) Porphyrin Complexes - Lo, Vanessa Kar-Yan; Thu, Hung-Yat; Chan, Yu-Man; Lam, Tsz-Lung; Yu, Wing-Yiu; Che, Chi-Ming (Synlett, 2012)
Rhodium(III) porphyrin complexes [Rh(Por)Me] are catalytically active towards stereoselective intramolecular carbene C–H insertions of α-diazoacetamides to give cis-β-lactams or trans-γ-lactams in yields up to 99% with regioselectivities up to 100% and cis/trans ratios up to 83:17 for β-lactams.
Keywords: rhodium porphyrin; carbene C–H insertion; stereoselectivity; intramolecular cyclization; lactams